Serum Vitamin D and B12 Deficiencies as Predictors of Thyroid Dysfunction: A Cross Sectional Analysis - Ahmed, Govand Ali (Journal of Sulaimani Medical College, 2025)
Background and Objectives: Thyroid disorders, including hypothyroidism and hyperthyroidism, are associated with micronutrient deficiencies, particularly vitamins D and B12. This study aimed to investigate the correlation between serum levels of vitamin D and vitamin B12 and thyroid status in patients with thyroid disorders. Methods: A cross-sectional study was conducted from January 2023 to June 2024 at a tertiary care hospital in a single center laboratory . A total of 250 participants, including patients with hyperthyroidism (n=52), hypothyroidism (n=99), and healthy controls (n=99), were enrolled. Serum levels of thyroid-stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3), vitamin D, and vitamin B12 were measured. Results: The mean age of patients with hyperthyroidism was 77.54 ± 17.928 years, while the mean age for those with hypothyroidism was 43.11 ± 14.839 years. The control group had a mean age of 38.79 ± 15.879 years. The correlation analysis revealed a weak, significant inverse relationship between TSH and both vitamin D and Vitamin B12 levels. Vitamin D was a significant predictor of hypothyroidism (OR = 1.17), indicating that each unit decrease in vitamin D increased the risk of hyperthyroidism by 17%. Similarly, vitamin B12 was also a significant predictor of hypothyroidism (OR = 1.08), with each unit decrease in vitamin D increasing the risk of hyperthyroidism by 8%. Conclusion: The study revealed a negative relationship between vitamin D and vitamin B12 serum levels in relation to TSH where higher vitamin concentrations corresponded to reduced TSH values.
Keywords: Effect; Hyperthyroidism; Hypothyroidism; TSH; Vitamin B12; Vitamin D